Diversity Training - Wildermuth, Cris; Gray, Susan (Association for Talent Development, 2005)
Traditionally, diversity education initiatives involve the catch phrase celebrate diversity. While the authors applaud this approach, this book offers a fresh perspective that focuses instead on the search for common ground among individuals and groups. In addition, the four fully scripted diversity modules allow you to develop a customized program quickly or enhance an existing diversity imitative. All ready-to-use PowerPoint slides, handouts, and other materials are included on a companion CD-ROM.